Cascade fragmentation of composite parent and child droplets. (1st February 2023) - Antonov, D.V.; Kuznetsov, G.V.; Voytkov, I.S.; Strizhak, P.A.; Volkov, R.S.
Highlights: The joint effect of adjacent droplets on their breakup regimes was observed. Sizes, velocities, energy, and composition of child droplets were calculated. Impact of temperature and sizes of child droplets on their breakup was determined. Conditions of cascade fragmentation of child and parent droplet were established. Correlations between the breakup delay times and sizes of child droplets were identified. Abstract: This paper presents the experimental findings on the consecutive cascade fragmentation of composite fuel droplets in a high-temperature gas. Using the breakup of typical two-liquid parent droplets as an example, we show the possibility of monotonous evaporation, puffing, and micro-explosion resulting in an array of secondary fragments of different sizes. The characteristics of these processes can be successfully controlled. A certain volume of a parent droplet can break up several times in the alternating puffing and micro-explosion regimes. The experiments were based on two-liquid parent droplets fixed on a designated holder in a high-temperature gas. The fragmentation of moving secondary droplets was recorded using tracking algorithms. The experimental findings were processed to obtain approximations of the experimental dependences of delay times between consecutive breakups, number of resulting droplets, their sizes, and other characteristics. A physical cascade fragmentation model was developed for a two-liquid droplet. Recommendations were formulated on how to ensure the intense cascade fragmentation of two-liquid droplets.